The Implementation of Corporate Social Responsibility (CSR) in Central Java Earthquake: A Preliminary Study on Consumer Belief, Attitude, and Purchase Intention - Kresno Agus Hendarto (Gadjah Mada International Journal of Business, 2009)
In Indonesia, Law No. 40/2007 paragraph 74 on Limited Liability Corporation regulates corporate social responsibility (CSR). Although CSR is mandatory for Indonesian resource-based firms, only four months after its enactment, six parties have asked for a judicial review to the Constitution Court as to the mandatory implementation of CSR. They argue that the mandatory implementation of CSR might result in legal uncertainty, render businesses inefficient, decrease competitiveness, and trigger discriminative treatments. Using the cases of CSR after the earthquake in Yogyakarta, this paper aims at answering the question of whether the implementation of CSR will lead to a decrease in competitiveness. Harnessing a mixed method of qualitative and quantitative approaches, this paper examines the models of beliefs, attitudes, and purchase intentions of consumers toward a company implementing CSR. The first phase of this study used a focus group discussion (FGD) to collect data from those who had benefited from CSR, and was analyzed using the content analysis. The results of the first phase then became the basis for the second phase. In the second phase, data were collected by surveying parents of school children whose school buildings were reconstructed by CSR programs, and answers were analyzed using the partial least squares analysis. Results show that the conjecture that the implementation of CSR will result in a decrease in competitiveness is not true. It is evident that CSR program affects the attitudes of consumers toward the firm, and that attitude fully mediates the relation between beliefs and purchase intentions toward the products of the firm implementing CSR.